INFLUÊNCIA DO TREINAMENTO CONCORRENTE DE CAPOEIRA E ATLETISMO NO DESEMPENHO MOTOR DE CRIANÇAS PRATICANTES DE FUTSAL - Evaldo Maciel Pinto; Diogo Guimarães; Athos Henrique Rocha Villaça; Sebastião Lobo Da Silva; Bibiano Madrid (Brazilian Army, 2012)
This study aimed to determine the influence of concurrent training and athletic capoeira levels of motor performance in children aged 7 to 10 years indoor football. Study participants were children (n = 39) were male. The subjects were divided into two groups, submitted to concurrent training, the AF group (n = 20) underwent the training of soccer and athletics and FC group (n = 19) soccer and capoeira. To study and evaluate the level of motor  performance of the two sample groups, we applied a battery of tests for statistical analysis and checked the normality of the data (Kolmogorov-Smirnov) and applied repeated measures ANOVA with post hoc Bonferroni. We used the statistical packages SPSS (12.0) and Instat (3.0). The results note that in terms of motor proficiency children who practiced FC compared to  children who practiced FA had equal values in the components of motor skills, however, both groups showed a trend in weight gain in their motor skills.